Distribution of Zakat through the Rumah Gemilang Indonesia Programme via the Networking Scheme - Usman, Nurodin; Janah, Nasitotul; Iman, Muis Sad (Universitas Islam Sultan Agung, 2025)
Among the challenges encountered by zakat institutions in Indonesia are traditional management practices and limited collaboration with other institutions. This study employs qualitative research methodologies to analyse the distribution of zakat with the aim of enhancing human resource quality through a networking framework involving fellow zakat institutions. The development model is manifested in the form of a flagship programme, Rumah Gemilang Indonesia (RGI) Magelang Campus, which results from collaboration between Lembaga Amil Zakat Dana Kemanusiaan Dhuafa (LAZ DKD) Magelang City and Lembaga Amil Zakat Nasional (LAZNAS) Al-Azhar Peduli Ummat Jakarta. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis involved a series of activities, including data reduction, data presentation, and deriving conclusions. The findings of the study indicate that network development is essential for zakat institutions to enhance their performance in fundraising and distribution programmes. The collaboration between LAZ DKD and LAZNAS Al-Azhar, exemplified by the Rumah Gemilang Indonesia (RGI) Magelang Campus, has demonstrated significant benefits that bolster the development of zakat management for both institutions. For LAZNAS Al-Azhar, the RGI Magelang Campus represents a key programme for zakat fund distribution, while for LAZ DKD, it serves as a leading initiative to foster closer ties with the community. The partnership between the two institutions continues to evolve, giving rise to additional pioneering programmes that are mutually beneficial and have empowering effects on the mustahiq. From an Islamic legal perspective, the distribution of zakat for the empowerment of the impoverished youth is permissible, as they are classified among the groups entitled to receive zakat. Through this training programme, it is anticipated that participants will emerge as individuals capable of paying zakat in the future.